Analyzing The Influence Of Pope's Tweets On His Followers' Mood - Ballona, Pedro Rego; Prado, Patrick; Almeida, Jussara Marques de; Marques-Neto, Humberto Torres Marques (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2015)
The ever-increasing usage of Social Medias, like Twitter, have enabled companies and public personalities to communicate and to influence their public. However, how to analyze and measure something as subjective as interpersonal influences? This paper presents a methodology for measuring and to analyze how Twitter’s posts (tweets) can influence their readers. In our work, the interpersonal influence of user is given by the capacity of tweets on influencing or affecting positively or negatively his/her mood or state of mind. Hence, the influence of one user A on another user B is the fluctuation of B’s mood when he/she reads and retweets a message posted by A. We measured the user’s mood using the Subjective Well-Being (SWB) that evaluates the mood of a person based on the positive and negative sentiment pointed on their collection of authored documents, e.g. on his/her thread of tweets. We applied the proposed methodology to analyze the influence of an important Twitter account, Your Holiness the Pope Francis, on the mood of his followers. The results show the existence of the Pope’s influence on his followers’ mood in a short-term period: from 1 to 2 hours after he/she retweets a Pope’s message.